2017
DOI: 10.1038/ejhg.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the peloponnesean populations and the theory of extinction of the medieval peloponnesean Greeks

Abstract: Peloponnese has been one of the cradles of the Classical European civilization and an important contributor to the ancient European history. It has also been the subject of a controversy about the ancestry of its population. In a theory hotly debated by scholars for over 170 years, the German historian Jacob Philipp Fallmerayer proposed that the medieval Peloponneseans were totally extinguished by Slavic and Avar invaders and replaced by Slavic settlers during the 6th century CE. Here we use 2.5 million single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
(6 reference statements)
4
20
0
Order By: Relevance
“…PCA revealed that GRBC unrelated patients map close to populations of European ancestry, particularly to the Iberian (IBS) and Tuscan (TSI) 1000 Genomes populations (Genomes Project et al, 2015) ( Figure 2 ). Although this finding derives from coding variants only, it is in line with work reporting genetic similarity between Greek and Italian subpopulations (Stamatoyannopoulos et al, 2017).…”
Section: Resultssupporting
confidence: 89%
“…PCA revealed that GRBC unrelated patients map close to populations of European ancestry, particularly to the Iberian (IBS) and Tuscan (TSI) 1000 Genomes populations (Genomes Project et al, 2015) ( Figure 2 ). Although this finding derives from coding variants only, it is in line with work reporting genetic similarity between Greek and Italian subpopulations (Stamatoyannopoulos et al, 2017).…”
Section: Resultssupporting
confidence: 89%
“…2 ). This is in line with studies using microarray analyses indicating a close relationship between European and south European populations [ 53 ]. As a result, these findings confirm the validity of the employed analysis method.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the previously obtained mapping results (Sequence Alignment/Map VCF format files: all samples reads were aligned to the gene regions of P. abies nuclear reference genomes), we used identity‐by‐descent (IBD) blocks to detect polymorphisms shared between individuals or lineages, under the algorithm from Beagle (Browning & Browning, ) with the following parameters: window = 1000, overlap = 100, ibdtrim = 100, ibdlod = 3 (Browning & Browning, ; Lazaridis et al ., ; Stamatoyannopoulos et al ., ). The number of markers per window, overlap between windows and number of trimmed markers were roughly doubled compared to the default parameters (Lazaridis et al ., ; Novikova et al ., ; Stamatoyannopoulos et al ., ). Mapping data were first phased into haplotypes by Beagle (Browning & Browning, ).…”
Section: Methodsmentioning
confidence: 97%
“…We computed the LOD score, which is the log 10 of the likelihood ratio. Candidate segments with LOD scores > 3.0 were treated as the strict IBD segments (Lazaridis et al ., ; Novikova et al ., ; Stamatoyannopoulos et al ., ). No IBD block was shared between P. breweriana and P. taeda based on a minimum LOD score of 3.…”
Section: Methodsmentioning
confidence: 97%